Comparative study on potential design parameter application of rainwater harvesting system on mosques / Ahmad Faiz Hassan Naziri ... [et al.] - Hassan Naziri, Ahmad Faiz; Zainonabidin, Azman; Mohamed Noor, Nur Azdli; Ismail, Dzulkarnaen (2022)
Tropical regions like Malaysia receive year-round rainfall, making it an appealing alternative to use rainwater as a resource. This country gets more than enough rain throughout the year, with an average rainfall around 3,000 mm a year, solely contributed by the hot and humid equatorial weather. In Malaysia, Rainwater Harvesting System (RWHS) has enormous potential for application, particularly in areas where water is heavily used, such as mosques. This study focused on examine and identify similarity and differences in term of application of RWHS for two different type of mosque in Perak. By using the design parameters (DPs) selected for both mosques, it can be identified that the execution for implementing RWHS would contrast for both mosques. The initial findings indicate that there are a different traits implied depending on the type of mosques and site context of the surrounding location, where difference in both mosques would play a huge role in installing the system. Ultimately, RWHS have the potential to provide significant impact on improving water savings for both mosques, with regards to proper calculation and method of installation are carried out thoroughly.